Analisis Kinerja Keuangan Usaha Sawmill Vina Lestari Jaya Di Tenggarong - Syahruddin Syahruddin (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2015)
Abstract:The purpose of this study was to determine the outline and assess the Company's financial performance Vina Lestari Jaya in 2004 compared to 2003 in terms of liquidity, solvency and profitability. How data collection techniques include interviews, observation and collection of data related to the data business, particularly financial data. Based on the analysis that has been submitted, it can be concluded that the hypothesis which says, "Performance Business Finance Sawmill Vina Lestari Jaya, in 2004 increased compared to 2003", accepted as true, although the result ratio obtained in 2004 a little less good for the ratio profitability when compared to 2003. However, the results obtained are not so great. Rise and fall of this ratio as a result of the sales growth rate in the last two years that turned out to be not in accordance with the sales growth rate of net profit growth tend to decline. The decline in the growth rate in net income was due to the increase in the growth rate of the cost of the post.Keywords: Liquidity, Solvency and Profitability